2012
DOI: 10.1111/j.1464-5491.2012.03597.x
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic exocrine function in patients with diabetes

Abstract: Factors associated with pancreatic exocrine failure differ in patients with Type 1 diabetes compared with patients with type 2 diabetes. In patients with Type 2 diabetes, association of decreased pancreatic exocrine function with BMI and vascular disease suggests a role of pancreatic arteriopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
78
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 30 publications
4
78
1
4
Order By: Relevance
“…An area of unresolved interest is why pancreata in long standing T1D are decreased in volume and mass in comparison to nondiabetic controls (37). Consistent with that data, exocrine function is also impaired in T1D (38). Hypotheses that have been put forward to account for these findings include loss of the growth promoting properties of insulin and subclinical pancreatitis (19).…”
Section: Discussionsupporting
confidence: 50%
“…An area of unresolved interest is why pancreata in long standing T1D are decreased in volume and mass in comparison to nondiabetic controls (37). Consistent with that data, exocrine function is also impaired in T1D (38). Hypotheses that have been put forward to account for these findings include loss of the growth promoting properties of insulin and subclinical pancreatitis (19).…”
Section: Discussionsupporting
confidence: 50%
“…litus patients have been reported to show a high prevalence of exocrine pancreatic insufficiency (22,23). Compared with diabetes mellitus patients, healthy individuals have a higher ␣-amylase level in the serum and a lower blood glucose level.…”
Section: Discussionmentioning
confidence: 99%
“…Tanaka et al reported that the CXCL10 and CXCR3, the receptors for CXCL10, activation circuit represents a unique mechanism of rapid beta-cell destruction in FT1DM (3). The possible causes of exocrine failure in patients with diabetes include an autoimmune process associated with type 1 diabetes, a direct trophic effect of insulin on the exocrine pancreas, microangiopathy and atherosclerosis (8). An investigation of the pancreatic exocrine function in a large cohort of patients with diabetes showed the primary factor associated with pancreatic exocrine failure in patients with typical autoimmune type 1 diabetes to be the duration of diabetes (8).…”
Section: Discussionmentioning
confidence: 99%
“…The possible causes of exocrine failure in patients with diabetes include an autoimmune process associated with type 1 diabetes, a direct trophic effect of insulin on the exocrine pancreas, microangiopathy and atherosclerosis (8). An investigation of the pancreatic exocrine function in a large cohort of patients with diabetes showed the primary factor associated with pancreatic exocrine failure in patients with typical autoimmune type 1 diabetes to be the duration of diabetes (8). This observation suggests that the mechanisms underlying exocrine failure in FT1DM patients are different from those underlying exocrine failure in patients with autoimmune type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%